Family Moral Values in Shaping Altruistic Behavior among Generation Z - Sinaga, Lamria (Universitas Muhammadiyah Metro, 2026)
Family moral values play a fundamental role in shaping altruistic behavior, particularly among Generation Z who grow up amid rapid social change and digital transformation. This study aims to examine the influence of family moral values on the formation of altruistic behavior among Generation Z. A qualitative phenomenological approach was employed, with data collected through in-depth interviews and participant observation involving individuals born between 1997 and 2012. The findings indicate that moral values such as empathy, responsibility, and solidarity are primarily internalized through parental role modeling and everyday family interactions. However, the consistency of moral practice tends to decline due to external influences, especially peer groups and social media exposure. The study highlights that while the family remains the primary foundation of moral development, explicit and open moral communication is increasingly necessary to reinforce altruistic behavior. Overall, this research affirms the enduring importance of family-based moral education in fostering socially responsible and empathetic young generations in the digital era.